2023
DOI: 10.1038/s42003-023-04907-x
|View full text |Cite
|
Sign up to set email alerts
|

Blood-feeding adaptations and virome assessment of the poultry red mite Dermanyssus gallinae guided by RNA-seq

Abstract: Dermanyssus gallinae is a blood-feeding mite that parasitises wild birds and farmed poultry. Its remarkably swift processing of blood, together with the capacity to blood-feed during most developmental stages, makes this mite a highly debilitating pest. To identify specific adaptations to digestion of a haemoglobin-rich diet, we constructed and compared transcriptomes from starved and blood-fed stages of the parasite and identified midgut-enriched transcripts. We noted that midgut transcripts encoding cysteine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 110 publications
0
9
0
Order By: Relevance
“…The most abundant TEs found in these tick species were long interspersed nuclear elements (LINEs), with 397,287 elements on average (∼7% of the elements identified). Interspersed sequences represented only 9.5% of the genome of Amblyomma maculatum (Ribeiro et al 2023), whereas they accounted for over 50% of the genome of all Ixodes ticks. However, the relative frequencies of each TE family were similar between the genomes of A. maculatum (Jose M. C. Ribeiro et al 2023) and I. scapularis (De et al 2023).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most abundant TEs found in these tick species were long interspersed nuclear elements (LINEs), with 397,287 elements on average (∼7% of the elements identified). Interspersed sequences represented only 9.5% of the genome of Amblyomma maculatum (Ribeiro et al 2023), whereas they accounted for over 50% of the genome of all Ixodes ticks. However, the relative frequencies of each TE family were similar between the genomes of A. maculatum (Jose M. C. Ribeiro et al 2023) and I. scapularis (De et al 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Interspersed sequences represented only 9.5% of the genome of Amblyomma maculatum (Ribeiro et al 2023), whereas they accounted for over 50% of the genome of all Ixodes ticks. However, the relative frequencies of each TE family were similar between the genomes of A. maculatum (Jose M. C. Ribeiro et al 2023) and I. scapularis (De et al 2023). For example, the Gypsy/DIRS family in the long terminal repeat (LTR) class has one of the highest coverages in both A. maculatum (Ribeiro et al 2023) and I. scapularis , (Nuss et al 2023, De et al 2023), and represent ∼5% of the genome in the four Ixodes species sequenced in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the microorganisms detected here may be endosymbionts, such as Bartonella -like bacteria, which covered between 30 % and 70 % of the sequences in the microbiome of D. gallinae collected from poultry houses in Czechia [ 7 , 20 ]. However, it has been previously demonstrated that Dermanyssus is capable of carrying and transmitting pathogenic Bartonella species to humans, such as Bartonella quintana [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dermanyssus gallinae is often considered a vector for several bacterial pathogens, such as Salmonella Gallinarum, Salmonella Enteritidis, Pasteurella multocida , Coxiella burnetii , and Spirochetes, as well as viral pathogens including Western equine encephalitis virus, and Venezuelan equine encephalitis virus [ [6] , [7] , [8] ]. Additionally, the poultry red mite has been found to test positive for various tick-borne pathogens (TBPs), although its ability to transmit them to other hosts has not been conclusively demonstrated [ 4 ].…”
Section: Introductionmentioning
confidence: 99%